Full-scale increased iron dosage to stimulate the formation of vivianite and its recovery from digested sewage sludge. (1st September 2020) - Prot, T.; Wijdeveld, W.; Eshun, L. Ekua; Dugulan, A.I.; Goubitz, K.; Korving, L.; Van Loosdrecht, M.C.M.
Abstract: The recovery of phosphorus from secondary sources like sewage sludge is essential in a world suffering from resources depletion. Recent studies have demonstrated that phosphorus can be magnetically recovered as vivianite (Fe(II)3 (PO4 )2 ∗8H2 O) from the digested sludge (DS) of Waste Water Treatment Plants (WWTP) dosing iron. To study the production of vivianite in digested sludge, the quantity of Fe dosed at the WWTP of Nieuwveer (The Netherlands) was increased (from 0.83 to 1.53 kg Fe/kg P in the influent), and the possible benefits for the functioning of the WWTP were evaluated. Higher Fe dosing is not only relevant for P-recovery, but also for maximal recovery of organics from influent for e.g. biogas production. The share of phosphorus present as vivianite in the DS increased from 20% to 50% after the increase in Fe dosing, making more phosphorus available for future magnetic recovery. This increase was directly proportional to the increase of Fe in DS, suggesting that vivianite could be favored not only thermodynamically, but also kinetically. Interestingly, analyses suggest that several types of vivianite are formed in the WWTP, and could differ in their purity, oxidation state or crystallinity. These differences could have an impact on the subsequent magnetic separation. Following the Fe dosing increase, P in the effluent and H2 S in the biogas both decreased: 1.28 to 0.42 ppm for P and 26 to 8 ppm for H2 S. No negative impact on the nitrogen removal, biogas production, COD removal or dewaterability was observed. Since quantification of vivianite in DS is complicated, previous studies were reviewed and we proposed a more accurate Mössbauer spectroscopy analysis and fitting for sludge samples. This study is important from a P recovery point of view, but also because iron addition can play a crucial role in future resource recovery wastewater facilities. Graphical abstract: Image 1 Highlights: Phosphorus recovery via vivianite can be enhanced through an increased iron dose. The additional dosed iron was nearly entirely transformed into vivianite. The extra iron dosing reduced the effluent P content to <0.5 mg P/L. The different types of vivianite found suggest different formation mechanisms. The method for vivianite quantification with Mossbauer spectroscopy was improved.